Kemampuan Menerjemahkan Teks Bahasa Indonesia Ke dalam Bahasa Makassar Pada Siswa Sekolah Menengah Atas - Novianti Agustina; Asia Asia; Sakinah Fitri (SOCIETIES: Journal of Social Sciences and Humanities, 2022)
Abstrak. This study discusses the ability to translate Indonesian text into Makassar language in class X SMAN 1 Bantaeng. The purpose of this study was to determine the students' ability in translating Indonesian text into Makassar language. This research is a type of quantitative research. The design in this research is descriptive quantitative. The data in this study are data in the form of student scores in translating Indonesian text into Makassar language. The data collection technique in this research is a written test technique. The results showed that the students were quite capable in translating Indonesian text into Makassar language Keywords: Students' ability in translating Indonesian text into Makassar language in class X SMAN 1 Bantaeng.